1994
DOI: 10.1007/bf00454728
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of inflammatory reaction in osteoid osteoma

Abstract: Between 1988 and 1993, 16 cases of osteoid osteoma were examined by magnetic resonance imaging (MRI). MRI clearly visualized the extent of inflammation in the bone marrow and soft parts that is difficult to observe with other diagnostic techniques. The degree of inflammation varied among the patients. This might be associated with the anatomical relationship between the nidus and the cortex. The high sensitivity of MRI, unfortunately, may lead to an erroneous interpretation in lesions accompanied by inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…These appearances can be confusing, although the mere presence and quantity of marrow and soft tissue edema are unreliable indicators of the biological potential of a lesion [16]. Features indicative of tumor-associated bone marrow edema are frequently found in benign disorders such as osteoid osteoma, osteoblastoma and chondroblastoma [16,17,18,19,20]. Weatherall et al [7] found 19 of 22 patients with chondroblastoma had bone marrow edema and a periosteal reaction was demonstrated in 18 patients, while Jee et al [6] reported 82% with similar features.…”
Section: Discussionmentioning
confidence: 99%
“…These appearances can be confusing, although the mere presence and quantity of marrow and soft tissue edema are unreliable indicators of the biological potential of a lesion [16]. Features indicative of tumor-associated bone marrow edema are frequently found in benign disorders such as osteoid osteoma, osteoblastoma and chondroblastoma [16,17,18,19,20]. Weatherall et al [7] found 19 of 22 patients with chondroblastoma had bone marrow edema and a periosteal reaction was demonstrated in 18 patients, while Jee et al [6] reported 82% with similar features.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins produced by the tumour result in a chronic inflammatory response in the surrounding tissues which is demonstrated by a periosteal reaction and synovitis. These regress spontaneously after removal of the nidus [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent use of MRI has not only allowed depiction of the nidus, but also provided information on accompanying phenomenon such as intramedullary intensity changes, peritumoral soft‐tissue intensity changes and retention of joint fluid in intra‐articular cases. However, the mechanisms of these phenomena remain unknown 3,4,12,13 …”
Section: Discussionmentioning
confidence: 99%